Исследования в крепости Ени-Кале - Куликов, А.В.; Бейлин, Д.В. (Археологічні дослідження в Україні, 2010)
In 2009, the expedition of the Crimean Branch of the IA NASU continued the excavations at Yeni-Kale Turkish fortress, at its southern, coastal area. The main stratigraphic stages of forming of the cultural layer, the original surface of the 18th c., and a gallery of underground drainage were traced. Based on the results of the work, recommendations for restoration and conservation of the objects in the fortress are given.